Identification of high-yielding brown planthopper-resistant aromatic rice lines through multi-trait selection - ANUSON THANASI; CHANTAMART CHUEAKAEW; SAKDA KONGSILA; EKASIT ONSAARDA; THEERAYUT TOOJINDA; SUREEPORN KATENGAM (Society for Indonesian Biodiversity, 2026)
Abstract. Thanasi A, Chueakaew C, Kongsila S, Onsaarda E, Toojinda T, Katengam S. 2026. Identification of high-yielding brown planthopper-resistant aromatic rice lines through multi-trait selection. Biodiversitas 27 (1): d270134. https://doi.org/10.13057/biodiv/d270134. Developing rice cultivars that combine durable resistance to brown planthopper (BPH; Nilaparvata lugens) with high and stable grain yield is essential for sustaining productivity in rainfed lowland ecosystems of the Mekong Basin. In Northeastern Thailand, rice cultivation is dominated by KDML105, a premium aromatic variety that is highly susceptible to BPH and increasingly vulnerable to climate-driven pest outbreaks and yield instability. This study evaluated 38 aromatic BPH-resistant (ABPH) rice lines developed through marker-assisted breeding under rainfed lowland conditions during the 2020 wet season. Significant genetic variation was detected among the evaluated lines for agronomic traits and yield components, with moderate to high heritability estimates, indicating substantial potential for effective phenotypic selection under target environments. Grain yield exhibited strong positive associations with key yield-determining traits, including spikelet number per panicle, tiller number, panicle length, harvest index, and spikelet fertility, highlighting their importance as indirect selection criteria under rainfed stress conditions. Multi-trait selection approaches integrating yield performance and resistance traits identified six elite ABPH rice lines that consistently combined superior grain yield with stable BPH resistance. These lines represent promising candidates for subsequent multi-environment trials and participatory on-farm evaluation. Overall, the findings demonstrate that integrating resistance breeding with multi-trait phenotypic selection is an effective strategy to accelerate the development of climate-resilient aromatic rice cultivars, contributing to reduced pesticide dependence, improved yield stability, and enhanced food security in rainfed lowland rice systems.